Classificação de singularidades semi- hiperbólicas e nilpotentes de campos planares analíticos - Scopel, Érick (2017)
In this work, we present some results of Qualitative Theory of Planar Ordinary Differential Equations employed in the investigation of the behavior of solutions in the neighborhood of semi-hyperbolic and nilpotent singularities.